1997
DOI: 10.1080/00103629709369802
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient deficiencies in rainfed calcareous soils of Pakistan. III. Boron nutrition of sorghum

Abstract: Boron (B) deficiency in crops is a major micronutrient disorder particularly in alkaline-calcareous soils. A nutrient indexing of rainfed sorghum [Sorghum bicolor (L.) Merr; cv. in the Potohar plateau of Pakistan revealed B deficiency in 50% of the 140 sampled fields in Jehlum district and 115 fields in Chakwal district. Hot water extractable (HWE) B in the associated soils, however, indicated more widespread B deficiency. The 255 sampled fields represented 21 soil series: 100 belonging to Alfisols, 63 to Ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
0
11
1
Order By: Relevance
“…Seed yield increases in groundnut have been reported from 9 to 12% by borax application in B deficient Chinese soil (0.3-0.5 mg B kg -1 ) by Zhang et al (1986). A 10% increase in pod yield of groundnut after B fertilization over the control) was obtained with 1 kg B ha -1 (Rashid et al, 1997) in Pakistan. Encouraging responses of groundnut to B application have also been recorded in India, with average pod yield increase of 180 kg ha -1 (Takkar & Nayyar, 1984).…”
Section: Groundnut/peanutmentioning
confidence: 97%
See 3 more Smart Citations
“…Seed yield increases in groundnut have been reported from 9 to 12% by borax application in B deficient Chinese soil (0.3-0.5 mg B kg -1 ) by Zhang et al (1986). A 10% increase in pod yield of groundnut after B fertilization over the control) was obtained with 1 kg B ha -1 (Rashid et al, 1997) in Pakistan. Encouraging responses of groundnut to B application have also been recorded in India, with average pod yield increase of 180 kg ha -1 (Takkar & Nayyar, 1984).…”
Section: Groundnut/peanutmentioning
confidence: 97%
“…Groundnut is also one of the important cash crops of the Potohar plateau in the Punjab province of Pakistan. The crop is grown under rainfed conditions on relatively poorly fertile alkaline-calcareous soils with no adequate fertilization history (Rashid et al, 1997). Its average yield in Pakistan is reported to be 921 kg ha -1 (Anonymous, 2009) and is much less as compared with the average yields of some other countries, e.g., in China, 2180 kg ha -1 (Luo et al, 1990).…”
Section: Groundnut/peanutmentioning
confidence: 99%
See 2 more Smart Citations
“…However, critical B concentration in 8-week-old whole shoots was much lesser (i.e., 37 mg B kg 2l ). In accordance with the guidelines provided by Reuter et al (1997) and Jones et al (1991), internal B requirement of young sunflower (a dicot) is much greater than similar-age plants of cereals (monocots), such as wheat (4 -6 mg B kg 21 ) (Rashid et al 2002b) and sorghum (17 -18 mg B kg 21 ) (Rashid et al 1997). The estimated internal B requirement of young plants, in this study, is even higher than the suggested critical concentration range for youngest fully expanded leaves of sunflower (i.e., 31 -38 mg B kg 21 ) (Blamey et al 1979).…”
Section: Boron Requirement Of Sunflowermentioning
confidence: 55%